OCCUPATIONAL ACCIDENTS WITH THE NURSING TEAM INVOLVED IN HOSPITAL CARE - Juliana Ladeira Garbaccio; Wiliam César Bento Regis; Rogério Magalhães Coimbra Silva; Wilson Goulart Estevão (Universidade Federal do Paraná, 2015)
This study aimed to describe occupational accidents in the nursing team of two public hospitals, and the notification of these. Transversal research was used, undertaken between March and April 2012, in the city of Arcos, in the Center-West of Minas Gerais. A structured questionnaire was applied to nurses, nursing technicians, and auxiliary nurses. The data were tabulated and analyzed descriptively and statistically using the Statistical Package for the Social Sciences software, version 13.0. The reporting of the rate of work accidents in the institutions, between 2002 and 2011, was 59.6%, of which 90% were of a biological nature, and 34% did not report the work accident. The youngest age range (20 - 29 years old/81.8%) and those with less length of experience (≤ 5 years/84.2%) reported more accidents. It is concluded that there is little adherence by the professionals to the care measures stipulated, it also being verified that a low percentage of Communication of Work Accidents forms were filled out, making educational and preventive interventions necessary in order to minimize accidents.